2013
DOI: 10.1002/jbm.a.34704
|View full text |Cite
|
Sign up to set email alerts
|

Different molecular weight hyaluronic acid effects on human macrophage interleukin 1β production

Abstract: This study examined the effect of hyaluronan (HA) molecular weight on immune response. HA with molecular weights ranging from the unitary disaccharide unit (400 Da) up to 1.7 × 10(6) Da and with very low endotoxin contamination level (less than 0.03 EU/mg) was used. Primary human monocyte/macrophage cultures were assayed for IL-1β production under a variety of inflammatory conditions with or without HA. Under the highest inflammatory states, production of interleukin 1β (IL-1β) was suppressed in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 45 publications
3
48
1
1
Order By: Relevance
“…1D). Our data are consistent with recent publications reporting that LMW HA does not stimulate chemokine production in the RAW 264.7 cell line, rat splenocytes, rat adherent differentiated primary macrophages, or primary human macrophages (28,29). rHuPH20 or LMW HA do not stimulate production of cytokines/chemokines in the air pouch model…”
Section: Lmw Ha Does Not Bind or Stimulate Tlr2 Or Tlr4supporting
confidence: 93%
See 1 more Smart Citation
“…1D). Our data are consistent with recent publications reporting that LMW HA does not stimulate chemokine production in the RAW 264.7 cell line, rat splenocytes, rat adherent differentiated primary macrophages, or primary human macrophages (28,29). rHuPH20 or LMW HA do not stimulate production of cytokines/chemokines in the air pouch model…”
Section: Lmw Ha Does Not Bind or Stimulate Tlr2 Or Tlr4supporting
confidence: 93%
“…Recent evidence that supports skepticism in this area is the observation that recombinant human hyaluronidase PH20 (rHuPH20), which degrades HMW to LMW HA fragments, did not stimulate IL-8 production in HUVECs (27). Other publications also showed that low endotoxin-containing HA fragments ranging from Mr 1,000 to 1,500,000 did not stimulate IL-1a production in primary human macrophages (28), or NO production in the murine cell line RAW 264.7, rat splenocytes, or rat adherent differentiated primary macrophages (29). HA at both high and low m.w.…”
mentioning
confidence: 99%
“…However, there is no direct evidence that LMW HA binds to TLR2 or TLR4, and some reports have suggested that if endotoxin (a putative stimulator of inflammation) is reduced to extremely low levels in purified preparations, LMW HA does not trigger normal tissue macrophage-mediated inflammatory reactions [15,16]. Our research clearly demonstrates that endotoxin-free LMW HA fragments (molecular weight range: 5-500 kDa) do not bind either TLR2 or TLR4; nor do these fragments stimulate TLR2-or TLR4-mediated nuclear factor-kappa-B (NF-kB) pathway signaling [3].…”
Section: Contaminant Hypothesismentioning
confidence: 99%
“…Possible sources of contamination include water, raw materials that contain lipopeptides, peptidoglycans, endotoxin, or other proteins. 14,22 Bacterial endotoxin is known to bind to other chemicals as well as to many surfaces, 23 revealing lower than tangible levels in the actual device. For example, the LAL assay could be exaggerated (3% HA of OVD) or underestimated (endotoxin-spiked dermal filler), especially in high-viscosity HA solutions or gels.…”
Section: Discussionmentioning
confidence: 99%
“…12 FDA researchers investigated the causes of TASS outbreaks as adverse events 13 ; and developed new testing methods to determine the inflammatory potential of suspected contamination of subject devices. [14][15][16][17][18][19][20][21] In 2012, Buchen et al evaluated an inflammatory potential of cohesive and dispersive OVDs which were spiked with known endotoxin concentrations, 13 and were measured using the LAL kinetic turbidimetric assay. Rabbits were given known concentrations of bacterial endotoxins mixed with HA and the researchers noted the concentration at which of endotoxin caused inflammation in the eye.…”
Section: Introductionmentioning
confidence: 99%